Comparison Study of the Mechanical, Thermal and Thermomechanical Properties of PVC Turkey Doors (Journal of the College of Basic Education, 2022)
In this study, the mechanical, thermal, thermomechanical properties as well as lifetime of two different companies of Turkey doors (Firat and Nova) have been measured. The tests were carried out on it, included: The (tensile, bending, impact, hardness, thermal conductivity, thermogravimetric analysis (TGA) and Thermomechanical analysis (TMA) tests).From the TGA curves the activation energy, thermal stability and lifetime are determined different heating rates (2, 5, 10, 20 and 40 ˚C/min), while the glass transition temperature (Tg) and softening point (Ts) are determined from (TMA) curves.The results showed that the Firat was overcome Nova in (mechanical, thermal conductivity, thermal stability and lifetime), while the glass transition temperature (Tg) and softening point (Ts) they have the same values.